1998
DOI: 10.1177/004947559802800212
|View full text |Cite
|
Sign up to set email alerts
|

Puerperal Sepsis: A Preventable Post-Partum Complication

Abstract: Patients with puerperal sepsis following delivery at Ife State Hospital (ISH) of Obafemi Awolowo University Teaching Hospitals Complex (OAUTHC) Ile-Ife over a 10-year period spanning January 1986 to December 1995 were reviewed. One hundred and forty-six patients were diagnosed as having puerperal sepsis and there were 8428 deliveries giving an incidence of 1.7%. The incidence was higher among the unbooked patients 71.2%. Predisposing factors were: anaemia in pregnancy, 69.2%; prolonged labour (labour lasting u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
3
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 4 publications
7
45
3
2
Order By: Relevance
“…Similar to our study, Dare FO et al [13], Shamshad et al [3] and Chandra Madhudas et al [7] found association between puerperal infection and prolonged labour and premature rupture of membranes however they did not correlate it with the grade of infection as was done in our study. However, Bako B et al [6] reported that major risk factors for developing puerperal sepsis as unbooked status in 88.0% and home delivery in 59.1%.…”
Section: Resultssupporting
confidence: 86%
“…Similar to our study, Dare FO et al [13], Shamshad et al [3] and Chandra Madhudas et al [7] found association between puerperal infection and prolonged labour and premature rupture of membranes however they did not correlate it with the grade of infection as was done in our study. However, Bako B et al [6] reported that major risk factors for developing puerperal sepsis as unbooked status in 88.0% and home delivery in 59.1%.…”
Section: Resultssupporting
confidence: 86%
“…12 We also observe that severe anemic patients developed wound infection in 16% cases , which is higher than study done by Riffat Jallelet al where it is only 7.8% but it is very minimal in comparision with study done by Dare FO and colleague 69.2%. 13 We found severe anemia significantly increases the risk of neo-natal complication. In this study the prevalence pre term delivery was 34% which is comparable with study done in south Africa.…”
Section: Discussionmentioning
confidence: 64%
“…The predisposing factors are anemia, low socioeconomic condition, prolonged labour, frequent vaginal examinations in labour, premature rupture of membranes for prolonged period. 5 Puerperal sepsis remains the common cause of maternal morbidity and mortality in developing countries and delay in detection and treatment may lead to obstetric shock and even death. Oliver Holmes, in 1843, was the first to establish that puerperal fever was contagious.…”
Section: Introductionmentioning
confidence: 99%